Assessment of Hematological Parameters in Sangamneri Goats during the Summer and Winter Season - Kokare, Saurabh; Mehere, Prajwalini V.; Patodkar, Vishwambhar R.; Sardar, Vikas M.; Jadhav, Sameer N.; Shelar, Raju R (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
The present study aims to evaluate heat stress's effects on haematological parameters in Sangamneri goats. Haematological parameters in domestic animals may be impacted by seasonal and environmental variations. Goats are recognized to be able to adapt to adverse situations. The Sangamneri Goat breed is an Indigenous native breed of the Sangamner region of the Ahmednagar district of Maharashtra, India. The investigation was carried out on six apparently healthy, female (non-pregnant, non-lactating ) adult Sangamneri goats with ages of 1 to 1.5 years and above, having similar body weight and maintained under semi-intensive framing system at Instructional Livestock Farm Complex (ILFC), K.N.P.College of Veterinary Science, Shirwal. Dist. Satara. Blood samples were collected at 0, 15, and 30 days during both the summer and winter seasons. The results revealed a significant increase in total leukocyte count (TLC) and the neutrophil-to-lymphocyte (N:L) ratio, particularly under summer conditions, indicating a stress-related response. Conversely, haemoglobin (Hb), packed cell volume (PCV) and total erythrocyte count (TEC) values were significantly elevated during the winter season. These alterations may be attributed to seasonal adaptive mechanisms, wherein the haematological parameters are modulated in response to environmental stressors. The observed changes suggest that Sangamneri goats exhibit physiological adjustments to cope with thermal variations, likely as part of a broader thermoregulatory and immunological adaptation process.